Clinical Predictors of Atheroma Progression Despite Optimal Glycemic Control in Early-Stage Diabetic Patients with Coronary Artery Disease: Insight from the DIANA Study - Yoshimasa, Yasunao; Kimura, Kazuo; Miyazaki, Shunichi; Kosuge, Masami; Kataoka, Yu; Sase, Kazuhiro; Yasuda, Satoshi; Miyamoto, Yoshihiro (Journal of Atherosclerosis and Thrombosis, 2014)
Aim: In the DIANA(DIAbetes and diffuse coronary NArrowing) study, which evaluated the impact of glucose-lowering therapy in early-stage diabetics with coronary artery disease(CAD), optimal glycemic control resulted in reduced disease progression on angiography. However, despite having a favorable glycemic status, some patients continued to exhibit disease progression. Factors associated with disease progression despite optimal glucose control remain to be elucidated. We sought to investigate clinical characteristics associated with substantial atheroma progression in early-stage diabetic patients with CAD who achieve favorable glycemic control. Methods: The DIANA study is a prospective randomized trial comparing the effects of lifestyle intervention and treatment with voglibose or nateglinide on disease progression on angiography in 302 CAD patients with impaired glucose tolerance/newly diagnosed diabetes. Of these patients, 137 CAD subjects who achieved optimal glycemic control were stratified according to the presence of disease progression on angiography: progressors(n=64) and non-progressors(n=73). Serial coronary angiography studies and quantitative coronary angiography analyses were conducted to evaluate disease progression. A multivariate analysis was performed to elucidate factors associated with disease progression. Results: Despite the achievement of optimal glycemic control, atheroma progression was observed in 46% of the study subjects. The progressors exhibited lower decreases in systolic blood pressure(SBP: p=0.007) and reduced baseline total lesion lengths(TLL: p=0.01). The multivariate analysis demonstrated that a greater increase in SBP(p=0.006), treatment without statins(p=0.03) and the baseline TLL(p=0.007) were independently associated with disease progression. Conclusions: Residual risk factors contribute to the progression of coronary atherosclerosis in early-stage diabetics who exhibit improvements in their glycemic status. The present findings underscore the need to intensively modify multiple risk factors during the early diabetic phase in order to prevent atheroma progression.